Association between obesity-associated markers and semen quality parameters and serum reproductive hormones in Chinese infertile men - Jian-Xiong Ma (Reproductive Biology and Endocrinology, 2020)
Abstract Background The current evidence on the association between obesity-associated markers and semen quality, serum reproductive hormones and lipids remains inconsistent. In this study, we tested the hypothesis that, in infertile Chinese men, body mass index (BMI) negatively correlates with sperm concentration, serum total testosterone (TT), and high-density lipoprotein cholesterol (HDL-C). The relationship between other obesity-associated markers and semen quality parameters, serum reproductive hormones, lipids and leptin were also investigated. Methods 181 Chinese infertile men were recruited from September 2018 to September 2019. Their obesity-associated markers, semen parameters, and serum reproductive hormones, lipids and leptin were detected. Statistical analysis was performed to assess the relationship between obesity-associated markers and semen quality, serum reproductive hormones, lipids and leptin. Result(s) Statistically negative correlation was found between other obesity-associated markers (e.g. waist-to-hip ratio and waist-to-height ratio) and semen parameters (e.g. sperm concentration, ratio of progressive motility and ratio of non-progressive motility), while no significant correlation was found between BMI and semen quality, serum reproductive hormones, lipids and leptin. Ratio of morphologically normal sperm was negatively correlated with serum lipids including total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), leptin and seminal superoxide dismutase. Ratio of progressive sperm, sperm concentration and ratio of morphologically normal sperm exhibited significantly lower values in overweight group than normal group. Estradiol (E2) and E2/TT were significantly higher in obese group than normal group, while TT level was significantly lower in obese group than normal group. Univariate and multivariate analysis indicated that TC was significantly associated with BMI. Serum leptin concentration was positively correlated with seminal leptin concentration in overweight and obese groups. Conclusion(s) No significant correlation was found between BMI and sperm concentration, serum TT and HDL-C, while other obesity-associated markers were found to negatively correlate with sperm concentration, ratio of progressive motility and ratio of non-progressive motility. Statistically significant correlations between serum reproductive hormones, lipids and leptin also existed in Chinese infertile men.